Marked population reduction in Antarctic fur seals challenges their Least Concern category - Jaume Forcada; Pete Bucktrout; Martin A. Collins; John Dickens; Michael Dunn; Nathan Fenney; Joseph I. Hoffman; Philip R. Hollyman; Anneke J. Paijmans; Andrew G. Wood (Biological Conservation, 2026)

Annual trends in mercury contamination are associated with changing trophic niches of giant petrels - William F. Mills; Danielle L. Buss; Paco Bustamante; Francisco Ramírez; Jaume Forcada; Manuela G. Forero; Richard A. Phillips (Environmental Research, 2025)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Ninety years of change, from commercial extinction to recovery, range expansion and decline for Antarctic fur seals at South Georgia - Jaume Forcada; Joseph I. Hoffman; Olivier Gimenez; Iain J. Staniland; Pete Bucktrout; Andrew G. Wood (Global Change Biology, 2023)
With environmental change, understanding how species recover from overharvesting and maintain viable populations is central to ecosystem restoration. Here, we reconstruct 90 years of recovery trajectory of the Antarctic fur seal at South Georgia (S.W. Atlantic), a key indicator species in the krill‐based food webs of the Southern Ocean. After being harvested to commercial extinction by 1907, this population rebounded and now constitutes the most abundant otariid in the World. However, its status remains uncertain due to insufficient and conflicting data, and anthropogenic pressures affecting Antarctic krill, an essential staple for millions of fur seals and other predators. Using integrated population models, we estimated simultaneously the long‐term abundance for Bird Island, northwest South Georgia, epicentre of recovery of the species after sealing, and population adjustments for survey counts with spatiotemporal applicability. Applied to the latest comprehensive survey data, we estimated the population at South Georgia in 2007–2009 as 3,510,283 fur seals [95% CI: 3,140,548–3,919,604] (ca. 98% of global population), after 40 years of maximum growth and range expansion owing to an abundant krill supply. At Bird Island, after 50 years of exponential growth followed by 25 years of slow stable growth, the population collapsed in 2009 and has thereafter declined by −7.2% [−5.2, −9.1] per annum, to levels of the 1970s. For the instrumental record, this trajectory correlates with a time‐varying relationship between coupled climate and sea surface temperature cycles associated with low regional krill availability, although the effects of increasing krill extraction by commercial fishing and natural competitors remain uncertain. Since 2015, fur seal longevity and recruitment have dropped, sexual maturation has retarded, and population growth is expected to remain mostly negative and highly variable. Our analysis documents the rise and fall of a key Southern Ocean predator over a century of profound environmental and ecosystem change.

A review of leopard seal (Hydrurga leptonyx) births and pups using a standardised age-class classification system - Krista van der Linde; Ingrid N. Visser; Rick Bout; Douglas J. Krause; Jaume Forcada; Donald Siniff; Sheridan Stone; Jim Fyfe; Nicolás Fernández-Ferrada; Kathryne Macallan; Oksana Savenko; Tracy E. Cooper (Polar Biology, 2022)
Despite the ecological importance of leopard seals ( Hydrurga leptonyx ) as apex marine predators, little is known about their reproductive biology. To address this paucity, we reviewed leopard seal birth and pup records and applied a standardised age-class classification system to differentiate between births/newborns (offspring ≤ 14 days old) and pups (> 14 days but < 6 months old). We compiled 19 birth/newborn and 141 pup records and examined their occurrence by month, region, substrate, birth-specific attributes (i.e. birth observations, fresh umbilicus or placental), standard length, weight, presence of mother, presence of lanugo, sex, status (e.g. born alive) and fate. These records indicate that leopard seal births occur between September and December, with peak records from September to November, whilst pup records peaked between August and December. The regions with the most birth/newborn records were the sub-Antarctic Islands (31.6%) and Chile (31.6%), followed by Antarctica (15.8%), New Zealand (15.8%) and the Falkland Islands (5.3%). Pups were recorded predominantly in the sub-Antarctic Islands (54.6%), followed by the Antarctic (42.6%), Chile (2.1%) and Australia (0.7%). Whilst leopard seal birth records were predominantly on ice, they were also found on terra firma . The northernmost published leopard seal birth records occurred in New Zealand whilst the northernmost published leopard seal pup records occurred in Australia. This study contradicts the long-standing hypothesis that leopard seals only give birth on Antarctic pack ice, and instead, here we indicate that 84.2% and 57.4% of collated leopard seal birth and pup records, respectively, occur outside of Antarctica. Our records illustrate the importance of northern regions as part of the leopard seal’s range. We emphasise the need to conduct research focused on the reproductive biology of this keystone species throughout its range and that future management of leopard seal populations should also consider their northern range.

Fur seal microbiota are shaped by the social and physical environment, show mother–offspring similarities and are associated with host genetic quality - Stefanie Grosser; Jan Sauer; Anneke J. Paijmans; Barbara A. Caspers; Jaume Forcada; Jochen B. W. Wolf; Joseph I. Hoffman (Molecular Ecology, 2019)
Despite an increasing appreciation of the importance of host–microbe interactions in ecological and evolutionary processes, the factors shaping microbial communities in wild populations remain poorly understood. We therefore exploited a natural experiment provided by two adjacent Antarctic fur seal ( Arctocephalus gazella ) colonies of high and low social density and combined 16S rRNA metabarcoding with microsatellite profiling of mother–offspring pairs to investigate environmental and genetic influences on skin microbial communities. Seal‐associated bacterial communities differed profoundly between the two colonies, despite the host populations themselves being genetically undifferentiated. Consistent with the hypothesis that social stress depresses bacterial diversity, we found that microbial alpha diversity was significantly lower in the high‐density colony. Seals from one of the colonies that contained a stream also carried a subset of freshwater‐associated bacteria, indicative of an influence of the physical environment. Furthermore, mothers and their offspring shared similar microbial communities, in support of the notion that microbes may facilitate mother–offspring recognition. Finally, a significant negative association was found between bacterial diversity and heterozygosity, a measure of host genetic quality. Our study thus reveals a complex interplay between environmental and host genetic effects, while also providing empirical support for the leash model of host control, which posits that bacterial communities are driven not only by bottom‐up species interactions, but also by top‐down host regulation. Taken together, our findings have broad implications for understanding host–microbe interactions as well as prokaryotic diversity in general.

A long-term study of gentoo penguin (Pygoscelis papua) population trends at a major Antarctic tourist site, Goudier Island, Port Lockroy - Michael J. Dunn; Jaume Forcada; Jennifer A. Jackson; Claire M. Waluda; Camilla Nichol; Philip N. Trathan (Biodiversity and Conservation, 2019)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Demographic parameters of black-browed albatrosses Thalassarche melanophris from the Falkland Islands - Paulo Catry; Jaume Forcada; Ana Almeida (Polar Biology, 2011)

Bet‐hedging response to environmental variability, an intraspecific comparison - Marie Nevoux; Jaume Forcada; Christophe Barbraud; John Croxall; Henri Weimerskirch (Ecology, 2010)
A major challenge in ecology is to understand the impact of increased environmental variability on populations and ecosystems. To maximize their fitness in a variable environment, life history theory states that individuals should favor a bet‐hedging strategy, involving a reduction of annual breeding performance and an increase in adult survival so that reproduction can be attempted over more years. As a result, evolution toward longer life span is expected to reduce the deleterious effects of extra variability on population growth, and consequently on the trait contributing the most to it (e.g., adult survival in long‐lived species). To investigate this, we compared the life histories of two Black‐browed Albatross ( Thalassarche melanophrys ) populations breeding at South Georgia (Atlantic Ocean) and Kerguelen (Indian Ocean), the former in an environment nearly three times more variable climatically (e.g., in sea surface temperature) than the latter. As predicted, individuals from South Georgia (in the more variable environment) showed significantly higher annual adult survival (0.959, SE = 0.003) but lower annual reproductive success (0.285 chick per pair, SE = 0.039) than birds from Kerguelen (survival = 0.925, SE = 0.004; breeding success = 0.694, SE = 0.027). In both populations, climatic conditions affected the breeding success and the survival of inexperienced breeders, whereas the survival of experienced breeders was unaffected. The strength of the climatic impact on survival of inexperienced breeders was very similar between the two populations, but the effect on breeding success was positively related to environmental variability. These results provide rare and compelling evidence to support bet‐hedging underlying changes in life history traits as an adaptive response to environmental variability.

First documentation of leopard seal predation of South Georgia pintail duck - Ewan W. J. Edwards; Jaume Forcada; Glenn T. Crossin (Polar Biology, 2010)

Penguin responses to climate change in the Southern Ocean - JAUME FORCADA; PHILIP N. TRATHAN (Global Change Biology, 2009)
Penguins are adapted to live in extreme environments, but they can be highly sensitive to climate change, which disrupts penguin life history strategies when it alters the weather, oceanography and critical habitats. For example, in the southwest Atlantic, the distributional range of the ice‐obligate emperor and Adélie penguins has shifted poleward and contracted, while the ice‐intolerant gentoo and chinstrap penguins have expanded their range southward. In the Southern Ocean, the El Niño‐Southern Oscillation and the Southern Annular Mode are the main modes of climate variability that drive changes in the marine ecosystem, ultimately affecting penguins. The interaction between these modes is complex and changes over time, so that penguin responses to climate change are expected to vary accordingly, complicating our understanding of their future population processes. Penguins have long life spans, which slow microevolution, and which is unlikely to increase their tolerance to rapid warming. Therefore, in order that penguins may continue to exploit their transformed ecological niche and maintain their current distributional ranges, they must possess adequate phenotypic plasticity. However, past species‐specific adaptations also constrain potential changes in phenology, and are unlikely to be adaptive for altered climatic conditions. Thus, the paleoecological record suggests that penguins are more likely to respond by dispersal rather than adaptation. Ecosystem changes are potentially most important at the borders of current geographic distributions, where penguins operate at the limits of their tolerance; species with low adaptability, particularly the ice‐obligates, may therefore be more affected by their need to disperse in response to climate and may struggle to colonize new habitats. While future sea‐ice contraction around Antarctica is likely to continue affecting the ice‐obligate penguins, understanding the responses of the ice‐intolerant penguins also depends on changes in climate mode periodicities and interactions, which to date remain difficult to reproduce in general circulation models.

Life history buffering in Antarctic mammals and birds against changing patterns of climate and environmental variation - JAUME FORCADA; PHILIP N. TRATHAN; EUGENE J. MURPHY (Global Change Biology, 2008)
The consequences of warming for Antarctic long‐lived organisms depend on their ability to survive changing patterns of climate and environmental variation. Among birds and mammals of different Antarctic regions, including emperor penguins, snow petrels, southern fulmars, Antarctic fur seals and Weddell seals, we found strong support for selection of life history traits that reduce interannual variation in fitness. These species maximize fitness by keeping a low interannual variance in the survival of adults and in their propensity to breed annually, which are the vital rates that influence most the variability in population growth rate ( λ ). All these species have been able to buffer these rates against the effects of recent climate‐driven habitat changes except for Antarctic fur seals, in the Southwest Atlantic. In this region of the Southern Ocean, the rapid increase in ecosystem fluctuation, associated with increasing climate variability observed since 1990, has limited and rendered less predictable the main fur seal food supply, Antarctic krill. This has increased the fitness costs of breeding for females, causing significant short‐term changes in population structure through mortality and low breeding output. Changes occur now with a frequency higher than the mean female fur seal generation time, and therefore are likely to limit their adaptive response. Fur seals are more likely to rely on phenotypic plasticity to cope with short‐term changes in order to maximize individual fitness. With more frequent extreme climatic events driving more frequent ecosystem fluctuation, the repercussions for life histories in many Antarctic birds and mammals are likely to increase, particularly at regional scales. In species with less flexible life histories that are more constrained by fluctuation in their critical habitats, like sea‐ice, this may cause demographic changes, population compensation and changes in distribution, as already observed in penguin species living in the Antarctic Peninsula and adjacent islands.

Population abundance, structure and turnover estimates for leopard seals during winter dispersal combining tagging and photo-identification data - Jaume Forcada; Sarah L. Robinson (Polar Biology, 2006)

Contrasting population changes in sympatric penguin species in association with climate warming - JAUME FORCADA; P. N. TRATHAN; K. REID; E. J. MURPHY; J. P. CROXALL (Global Change Biology, 2006)
Climate warming and associated sea ice reductions in Antarctica have modified habitat conditions for some species. These include the congeneric Adélie, chinstrap and gentoo penguins, which now demonstrate remarkable population responses to regional warming. However, inconsistencies in the direction of population changes between species at different study sites complicate the understanding of causal processes. Here, we show that at the South Orkney Islands where the three species breed sympatrically, the less ice‐adapted gentoo penguins increased significantly in numbers over the last 26 years, whereas chinstrap and Adélie penguins both declined. These trends occurred in parallel with regional long‐term warming and significant reduction in sea ice extent. Periodical warm events, with teleconnections to the tropical Pacific, caused cycles in sea ice leading to reduced prey biomass, and simultaneous interannual population decreases in the three penguin species. With the loss of sea ice, Adélie penguins were less buffered against the environment, their numbers fluctuated greatly and their population response was strong and linear. Chinstrap penguins, considered to be better adapted to ice‐free conditions, were affected by discrete events of locally increased ice cover, but showed less variable, nonlinear responses to sea ice loss. Gentoo penguins were temporarily affected by negative anomalies in regional sea ice, but persistent sea ice reductions were likely to increase their available niche, which is likely to be substantially segregated from that of their more abundant congeners. Thus, the regional consequences of global climate perturbations on the sea ice phenology affect the marine ecosystem, with repercussions for penguin food supply and competition for resources. Ultimately, variability in penguin populations with warming reflects the local balance between penguin adaptation to ice conditions and trophic‐mediated changes cascading from global climate forcing.

USE OF PHOTOGRAPHIC IDENTIFICATION IN CAPTURE‐RECAPTURE STUDIES OF MEDITERRANEAN MONK SEALS - Jaume Forcada; Alex Aguilar (Marine Mammal Science, 2000)
A bstract The use of photo‐identification and its reliability in capture‐recapture studies of Mediterranean monk seals were assessed using slides collected in the colony at Cap Blanc, western Sahara, from 1993 to 1996. Five tests indicated that researchers involved in photo‐identification were proficient in matching slides of identified seals, consistent in classifying the side of the seal shown in slides and in assigning the morphological stage of the seal, and that changes of markings over a period of three years were insufficient to affect matching success. The certainty of identifying a seal was not dependent on the number of slides used but on distinctiveness of the markings and the quality of the slides taken. Capture‐recapture abundance estimates were biased upwards when including poor quality slides. The exclusive use of excellent‐ and good quality slides provided the best estimates. The proportion of distinctive seals varied between morphological stages and was significantly lower in juveniles. When including the identification histories of juveniles, the heterogeneity of capture probabilities was higher. Therefore, abundance estimates were less biased when all juveniles were considered as non‐distinctive seals. Reliable abundance estimates required a balance between duration of capture occasions and time interval between these.